Evaluation of the Council to Improve Foodborne Outbreak Response (CIFOR) Guidelines for foodborne disease outbreak response and associated toolkit - Ringel, Jeanne S.; Huang, Christina Y.; Morganti, Kristy Gonzalez (Research report (Rand Corporation), 2013)
Foodborne disease is a significant public health problem. Estimates from the U.S. Centers for Disease Control and Prevention (CDC) indicate that, in 2011, approximately one in six individuals in the United States was affected by a foodborne disease, resulting in 127,839 hospitalizations and roughly 3,000 deaths (Centers for Disease Control and Prevention, 2011; Scallan et al., 2011). With reducing the burden of foodborne disease among its primary goals, CIFOR developed the Guidelines for Foodborne Outbreak Response (2009) and a companion Toolkit (2011) to facilitate improvements in foodborne disease outbreak detection and response at the state and local levels. The objective of this study is to assess the distribution and use of the CIFOR Guidelines and Toolkit to determine whether and to what extent they are reaching their intended users and achieving their intended goals. Findings from this evaluation provide important information about how the dissemination, content, and structure of the Guidelines and Toolkit can be changed to facilitate their use and further improve foodborne outbreak response.